Village Survey Monographs, Keladi Village, No-9, Part VI, Vol-XI - Balasubramanyam, K. (Karnataka, 1961)
Village, People and their Material Equipments, Economy of the Village, Social and Cultural life.
Keywords: Sagar Taluk; Shimoga District